The Influence of Social Media Marketing and Perceived Quality on KFC Brand Equity (Consumer Study KFC Mulyosari Surabaya) - Aida Kurnia Sari; Rizky Dermawan (Indonesian Journal of Business Analytics, 2023)
This study aimed to determine the influence of social media marketing and perceived quality on KFC brand equity. This study makes use of quantitative research techniques and the KFC Mulyosari Surabaya customer population. Using a purposive sampling technique and non-probability sampling, a sample of 130 respondents was chosen. The sample consists of respondents who often visit and buy KFC at KFC Mulyosari Surabaya outlets at least once a month, actively follow KFC Instagram social media, and are over 17 years old. Primary as well as secondary data were used in this study. Partial least square (PLS) analysis was employed in this study along with validity, reliability, and hypothesis testing tests. The conclusions of this study prove that social media marketing and perceived quality have a positive and significant influence on brand equity.